Composite Fertilizer Management Index (CMFI) among Major Field Crop Growers of Telangana - Kemekar, Pavankumar; Ch. Venu Gopala Reddy,; K. Madhu Babu,; K. Suhasini,; A. Meena,; A. Madhavi, (Indian Journal of Extension Education, 2025)
The study was conducted during 2023–2025 to develop a composite fertilizer management index (CFMI) for major field crops of Telangana, encompassing planning, purchasing, practicing, and performance dimensions. The research design involved 360 farmers across six major field crops i.e. paddy, cotton, maize, red gram, soybean, and Bengal gram. Data on 22 indicators were collected from farmers, normalised and analyzed using Principal Component Analysis (PCA), Kruskal-Wallis test, and Multivariate General Linear Model (GLM). Results revealed that maize farmers ranked highest in overall fertilizer management (CFMI = 0.49), followed by paddy (0.48), red gram (0.46), cotton (0.44), soybean (0.30), and Bengal gram (0.29). Significant difference in fertiliser management across crops (χ² = 123.136, p < 0.01) was found. Education, farming system, experience in selected crop cultivation, manure and fertilizer availability, social participation, extension contact, scientific orientation, sustainability orientation and economic motivation were key determinants of CFMI (R² = 0.643). The findings highlight the need to enhance farmers’ knowledge and attitudes toward efficient fertilizer practices, raise awareness of health and environmental impacts, and strengthen input availability and institutional linkages to promote balanced nutrient management and improve soil health, crop productivity, and resource use efficiency.